Nonaqueous Enteric Coating Application of HPMC and Eudragit L100 on Hard Gelatin Capsules: Designed to Achieve Intestinal Delivery - Swamykannu Dinesh Mohan, V. R. M. Gupta, Harika yasam, Yamini jampani, Manaswini Yalamanchili (Journal of Applied Pharmaceutical Science, 2015)
Omeprazole (OMZ) is a weak base proton pump inhibitor and it can be easily broken down in the acidic location before reaching to the small intestine where it is absorbed. Therefore, the main aim of this investigation is to protect the drug in the stomach environment with the object of exhibiting 100% drug release at the site of absorption. Prior to coating all the capsules were filled with API and other suitable excipients then placed on to the lab model conventional coating pan. Two different polymers such as (HPMC) and Eudragit L 100 were selected for this study. First, the pre coating solution (HPMC) was employed after drying enteric coating solution (Eudragit L 100) was applied under suitable coating parameter finally over coating solution of (HPMC) was applied and kept for drying. Different coating thickness ranges from 38.33 to 89.75% was observed by Scanning electron microscopy and tested for acid uptake test, disintegration and dissolution tests in pH 1.2 HCl media for 2 hours and pH 6.8 phosphate buffer solution. Less coating thickness capsules were allowed to penetrate the acid and the capsules were ruptured in an acid environment, therefore early drug release was occurred in acid media. Whereas capsules with high coating thickness of 89µm were not allowed acid to penetrate this indicates that the drug could be protected from degradation in the gastric environment.
Keywords: Omeprazole, HPMC, Eudragit L 100, HCl and Coating pan.